Influência do tempo e do tratamento da superfície do parafuso protético de retenção do pilar nos valores de destorque - Machado, Emerson Teixeira (2009)
Problem: The screw loosening on abutment of retention represents a risk factor in implants prosthodontics. Purpose: The aim of this study was verify the torque of detach the abutment screw with two types of surface treatment to compared the screw without treatment. Material and Method: External hexagon implants (13mm-length, 4,1mm-diameter) were mounted in PVC rings and received screw fixed partial prosthesis with one cantilever unit (10mm). All prostheses were cast Ni-Cr-Be alloy and torque tightened to 35N/cm. Detorques were registered immediate torque, after five and thirty- minute intervals. Results: Significant statistically differences between detorque group without treatment, DLC and future treatment were observed in the study. All samples and groups without surface treatment obtain less performance. Conclusion: The time and the abutment screw surface influences on detorque values. Clinical Implications: Abutments screw without treatment must be evitable in implants abutments.